"Am I Doing This Right?": A Qualitative Exploration of How College Men Make Meaning of Gendered Expectations. (December 2018) - Foste, Zak; Davis, Tracy L.
Existing scholarship illustrates a rather consistent picture of how cisgender collegiate men understand what it means to be a man in college. Less is known, however, about how these college men make sense of such expectations. This qualitative study examined the ways in which meaning-making capacities influenced how participants made meaning and interacted with gendered expectations. Our results indicate a clear understanding of how participants define the external expectations of gender in college. How participants were influenced by these expectations was largely dependent on meaning-making capacities. We offer three developmental phases that capture how participants made sense of gendered expectations: passive constructions, reactionary constructions, and movement toward proactive constructions.